(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Miraculous birth: Standing at just 35"(104.14cm) tall, 28 years old proportionate dwarf lady weighing 20 kg was succeeded in giving birth to a girl at 36+ weeks of pregnancy by cesarean section in June, 2013 making her the smallest woman ever reported to give birth to apparently healthy looking, and average-sized female baby in Bangladesh. Detailed clinical examination of the neonate performed by the neonatologist revealed no obvious external congenital anomalies and infantogram after 6 weeks also revealed normal study. J. Paediatr. Surg. Bangladesh 4(2): 72-75, 2013 (July)